2011
DOI: 10.1097/ccm.0b013e318206b9be
|View full text |Cite
|
Sign up to set email alerts
|

Hypertonic saline versus mannitol for the treatment of elevated intracranial pressure: A meta-analysis of randomized clinical trials*

Abstract: We found that hypertonic saline is more effective than mannitol for the treatment of elevated intracranial pressure. Our meta-analysis is limited by the small number and size of eligible trials, but our findings suggest that hypertonic saline may be superior to the current standard of care and argue for a large, multicenter, randomized trial to definitively establish the first-line medical therapy for intracranial hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
144
2
11

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 312 publications
(159 citation statements)
references
References 44 publications
2
144
2
11
Order By: Relevance
“…One review, as with ours, concluded that hypertonic saline solution has no effect on mortality 21 ; another study reporting on mortality suggested a decreased mortality with the use of hypertonic saline. 16 With regards to the five systematic reviews evaluating intracranial pressure management, they identified a reduction in intracranial pressure [16][17][18][19][20] associated with hypertonic saline solution, in contrast with our results. These discrepancies may be due to several factors.…”
Section: Discussioncontrasting
confidence: 77%
See 3 more Smart Citations
“…One review, as with ours, concluded that hypertonic saline solution has no effect on mortality 21 ; another study reporting on mortality suggested a decreased mortality with the use of hypertonic saline. 16 With regards to the five systematic reviews evaluating intracranial pressure management, they identified a reduction in intracranial pressure [16][17][18][19][20] associated with hypertonic saline solution, in contrast with our results. These discrepancies may be due to several factors.…”
Section: Discussioncontrasting
confidence: 77%
“…[16][17][18][19][20][21] All reviews posed a different clinical question and used different inclusion criteria. One review, as with ours, concluded that hypertonic saline solution has no effect on mortality 21 ; another study reporting on mortality suggested a decreased mortality with the use of hypertonic saline.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hyperosmolar therapy with either hypertonic saline or mannitol should be considered in cases where mass effect from significant edema is noted. We favor hypertonic saline over mannitol and, though no randomized clinical trials exist, a meta-analysis has supported this practice [138]. Two percent sodium (Na) solution can be given through a peripheral line, while 3 % or 23.4 % Na should be given through a central line.…”
Section: Edema and Herniationmentioning
confidence: 99%